Analisis Dampak Budaya Organisasi Terhadap Efektivitas Program Pelatihan Kepemimpinan dan Pengembangan SDM Mahasiswa FEB Universitas Sultan Ageng Tirtayasa - Vera Maria; Nisrina Khalda Turnip; Alya Malika Putri; Febri Haerurrohman (Journal Economic Excellence Ibnu Sina, 2025)
Leadership training and human resource (HR) development for students of the Faculty of Economics and Business (FEB) at Sultan Ageng Tirtayasa University (Untirta). Organizational culture has an effect on development programs, such as leadership training. this factor is very important in achieving success. This research method uses a descriptive quantitative approach by collecting data through questionnaires given to students who take part in leadership training programs at FEB Untirta. The analysis shows that organizational culture that supports collaboration, innovation, and openness has a positive effect on the effectiveness of leadership training programs. In contrast, organizational customs that tend to be hierarchical and unchangeable can hinder the development of students' human resources. This study assists training program managers at FEB Untirta in developing approaches that are in line with organizational culture to improve leadership training outcomes and student human resource development in the future.